National and foreign research of Anaferon Kid: efficacy, safety and experience of application (review) - Yu. V. Lobzin; F. De. Rosa; E. V. Esaulenko (Журнал инфектологии)
Interest in acute respiratory viral infections (ARVI) in children does not tend to decrease and is determined by their high prevalence, relatedness to «uncontrollable infections» in most cases and presence of age limits in the use of antiviral drugs. Presently, focus on the use of national drugs is made in the RF clinical practice. An innovative drug Anaferon for children was developed by the Russian pharmaceutical company OOO «NPF «Materia Medica Holding» and registered in Russia in 2002.The summary purpose is to classify and analyze national and international publications on the results of non-clinical and clinical investigation of Anaferon for children efficacy and safety in ARVI and other viral infections.Study method: exploratory and analytical.Results: the summary presents the data of non-clinical studies justifying the drug mechanism of action at molecular level ensuring its combined antiviral and immunomodulating efficacy. The results obtained in the experiment were verified by clinical studies and are reflected in numerous scientific publications including international ones. The summary contains analysis of the results of clinical studies of the drug in children with ARVI including influenza. Anaferon for children was found to reduce duration of the main clinical symptoms of ARVI and influenza, incidence of bacterial complications, it is well-tolerated and has high safety profile. The open-label randomized comparative study of Anaferon for children efficacy and safety vs. Oseltamivir in influenza demonstrated clinical efficacy of these drugs. Numerous publications evidence that Anaferon for children exerts antiviral effect against most viruses causing acute respiratory viral infections as well as herpes viruses, viruses causing intestinal infections and tick-borne encephalitis. The list of scientific publications on the drug consists of approximately 800 references including more than 50 articles in foreign languages, particularly in journals with high citation index.